2013
DOI: 10.2298/sarh1304178t
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells isolated from peripheral blood and umbilical cord Wharton’s jelly

Abstract: The results obtained demonstrated that both MSCs represent good alternative sources of adult MSCs that could be used in cell therapy applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 30 publications
1
47
0
Order By: Relevance
“…Conversely, the use of MSCs is free of such ethical concerns and requires less stringent criteria for transplantation [1]. MSCs are stem cells of stromal origin characterized by their multipotency with the ability to self-renew [2] [3] and differentiate to diverse cell phenotypes such as osteoblasts, chondrocytes, adipocytes, fibroblasts, tenocytes [4] [5], hepatocytes, neural cells and/or epithelial cells [6]. Due to their crucial regenerative, reparative, angiogenic and immunomodulatory properties, MSCs have generated increased interest in a variety of biomedical disciplines and several areas of experimental and clinical applications [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, the use of MSCs is free of such ethical concerns and requires less stringent criteria for transplantation [1]. MSCs are stem cells of stromal origin characterized by their multipotency with the ability to self-renew [2] [3] and differentiate to diverse cell phenotypes such as osteoblasts, chondrocytes, adipocytes, fibroblasts, tenocytes [4] [5], hepatocytes, neural cells and/or epithelial cells [6]. Due to their crucial regenerative, reparative, angiogenic and immunomodulatory properties, MSCs have generated increased interest in a variety of biomedical disciplines and several areas of experimental and clinical applications [2].…”
Section: Introductionmentioning
confidence: 99%
“…MSCs are stem cells of stromal origin characterized by their multipotency with the ability to self-renew [2] [3] and differentiate to diverse cell phenotypes such as osteoblasts, chondrocytes, adipocytes, fibroblasts, tenocytes [4] [5], hepatocytes, neural cells and/or epithelial cells [6]. Due to their crucial regenerative, reparative, angiogenic and immunomodulatory properties, MSCs have generated increased interest in a variety of biomedical disciplines and several areas of experimental and clinical applications [2]. Surely, marrow MSCs (BM MSCs) have been the most widely studied; however MSCs can be also isolated, with similar but not identical features, from different tissues including umbilical blood cord (UCB MSCs), placenta, adipose tissue (AT MSCs), trabecular bone, dental pulp and peripheral blood (PB MSCs) [7]- [12].…”
Section: Introductionmentioning
confidence: 99%
“…In our laboratory MSCs from adipose tissue, dental pulp of deciduous teeth, peripheral blood and Wharton's jelly of umbilical cord were recently isolated and characterized exhibiting typical MSC morphology, clonogenic potential, immunophenotype and multipotent capacity to differentiate along mesenchymal lineages (osteogenic, chondrogenic, adipogenic and myogenic) in vitro [10,11]. It is known that MSCs isolated from different tissues have similar but not identical capacity to modulate immune response.…”
Section: Discussionmentioning
confidence: 99%
“…MCSs from human dental pulp of deciduous teeth (DP-MSCs), peripheral blood (PB-MSCs), umbilical cord Wharton's jelly (UC-MSCs), as well as from adipose tissue (AT-MSCs), were isolated and their MSCs identity confirmed as previously described [10,11].…”
Section: Mscs Isolation and Culturementioning
confidence: 99%
“…These cells continue to have their normal karyotype after multiple cycles of cell division (Mitchell et al 2003;Can and Karahuseyinoglu 2007). These cells could also differentiate in to other cells including osteoblasts, adipocyte, myocyte, and endothelial progenitor cells (Shen et al 2013;Trivanović et al 2013). Researches showed that MSCs obtained from this region have the potential to express neuronal markers and could be a suitable source for treating the symptoms of Parkinson disease (Fu et al 2006).…”
Section: Introductionmentioning
confidence: 99%